Preparation and Screening of Cross-Linked Magnetic Biocarbon for Methylene Blue Removal - Gan SuTeng (2019)
A cross-linked iron oxide particle with activated biocarbon (MAC) by Cetyltrimethylammonium Bromide (CTAB) and Cyclopentasiloxane (CPS) was designed for the uptake of Methylene Blue (MB) in water solution. The cross-linked MAC was successfully prepared with strong magnetization property. The effect of contact time of MB onto newly prepared MAC samples was screened and studied. The removal effectiveness also compared with MAC (T1), AC (positive control), and provided MAC (pMAC) (negative control). The physical and chemical properties of studied samples were obtained through iodine test, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscope equipped with energy-dispersive spectroscopy (SEM-EDS), and thermogravimetric analysis (TGA). MAC cross-linked with CPS (MAC-CPS) showed highest efficiency in MB removal of 99.84 % in 60 min relative to CTAB cross-linking agent (MAC-CTAB). However, low iodine number obtained in MAC-CPS as 90.18 mg/g decreased compared to AC and MAC as 1007.01 mg/g and 240.48 mg/g respectively. The FTIR spectrum of MAC-CPS indicated intense of Si-O stretching and Fe-O stretching at 1254 cm-1 and 525 cm-1 respectively. This can be assigned to the interaction between iron oxide and CPS in cross-linked reaction. The analysis of XRD suggested that the main magnetic phase present is magnetite (Fe3O4) with small amounts of maghemite (γ-Fe2O3). The TGA demonstrates MAC-CPS possessed higher thermal stability property. The excellent characteristics presented by CPS potential as cross-linking agent for further practical applications.